“Hey Mitch-elle, you need a shave!”: The school days of hirsute adolescents - Nelson, Adie; Nelson, Veronica (Qualitative Sociology Review, 2010)
This qualitative, longitudinal study directs attention to how adolescence – a time period that is already fraught with pressures and struggles for most – may be complicated by the presence of hirsutism, a putatively “sexdiscordant” marker. Attention is directed to the school-based experiences of a non-representative sample of 67 Canadian youth and 41 adult women who shared their recollections of how hirsutism had impacted their lives as adolescents. Although hirsute youth may seem well-situated to act as the trailblazers for the type of subversive crossings that Butler (1990) championed in Gender Trouble, our study find little to suggest that they would welcome this role. Rather, the obverse seems true. However, given the dependent status of adolescents in Western society, it might be entirely presumptuous to expect hirsute youth to behave as if dualistic thinking about sex, gender and sexuality did not exist when so many of their experiences will continuously remind them that it does.